Incorporating the voice of the child into clinical assessments for children in need - Katie Newman; Shanti Raman; Allison Ward (Child Protection and Practice)
Background: Upholding the voice of the child (VOC) in clinical encounters is critical to realising their rights. Evidence from inquiry reports however demonstrate that practitioners fail to adequately listen to the voice of the child in the child protection process, with a paucity of clinical protocols incorporating children's voices. Objective: We aimed to develop a clinical protocol for incorporating the VOC in Community Paediatric clinical assessments and evaluate the VOC protocol. Methods: Drawing upon work carried out in London on child protection medical assessments, we used quality improvement methodology to incorporate VOC protocols in South Western Sydney's (SWS) specialised Community Paediatric clinics for vulnerable children and young people (CYP). A VOC-focused protocol guiding clinical assessments and report writing was developed for SWS Community Paediatric Clinics. Following training of clinicians, the protocol and report template was trialled over a 6-month period. We audited 40 clinic reports before and after introduction of the protocol. We interviewed referring agents and clinicians involved in these clinics to explore enablers and barriers to incorporating the VOC clinically. Findings: Baseline audits of reports revealed that CYP were given some presence in 80 % of reports, but voices seldom recorded. Following the VOC trial, there was overall improvement in practice, with VOC recorded 65 % of the time, CYP's views and recommendations acknowledged in 88 % of reports. Clinicians and referring agents reported that the active inclusion of CYP voices in assessments was highly valued. Conclusions: Incorporating CYP's voices into the clinical assessment process is feasible and celebrates best practice.